Reconstruction of rotatory moving image from projections - Imiya, A.; Nakayama, Y.; Yamamoto, Y. (Pattern Recognition, 9th International Conference on, 1988: Proceedings, 2003)
A tomographic reconstruction technique for a moving image produced by a rotating camera is presented. Projections of the moving image are degraded because of image movement. It is clarified that projection of a moving image are convolved by the kernel function defined by the angular velocity of an image. A reconstruction method is derived for a clear image from degraded projections. An estimation method of the angular velocity is also proposed.< >